Exploring riparian vegetation interactions with flow regime and fluvial processes for an improved river management and conservation - Silva, Rui Pedro Guerreiro Duarte Rivaes da (2019)
Doutoramento em Restauro e Gestão Fluviais - Instituto Superior de Agronomia / Faculdade de Arquitetura / Instituto Superior Técnico